Evaluation of the relative effectiveness of the 2017 updated Manchester scoring system for predicting BRCA1/2 mutations in a Southeast Asian country - Chew, Winston; Moorakonda, Rajesh Babu; Courtney, Eliza; Soh, Hazel; Li, Shao Tzu; Chen, Yanni; Shaw, Tarryn; Allen, John Carson; Evans, Dafydd Gareth R; Ngeow, Joanne (Journal of medical genetics, 2018)
BackgroundGermline mutations in the BRCA1 and BRCA2 genes have significant clinical implications for both risk-reducing and early surveillance management. The third and most recent revision of the Manchester scoring system (MSS3) used to distinguish patients indicated for germline BRCA1/2 testing included further adjustments for triple negative breast cancer, high-grade serous ovarian cancer and human epidermal growth factor 2 (HER2) receptor status. This study aims to evaluate the relative effectiveness of MSS3 in a Southeast Asian population.MethodsAll patients in our centre were tested using next-generation sequencing (NGS) panels that included full gene sequencing as well as coverage for large deletions/duplications in BRCA1/2. We calculated MSS1-3 scores for index patients between 2014 and 2017 who had undergone BRCA1/2 genetic testing and recorded their genetic test results. MSS1-3 outcomes were compared using receiver operating characteristic analysis, while associations with predictors were investigated using Fisher’s exact test and logistics regression. Calculations were performed using Medcalc17.ResultsOf the 330 included patients, 47 (14.2%) were found to have a germline mutation in BRCA1 or BRCA2. A positive HER2 receptor was associated with a lower likelihood of a BRCA1/2mutation (OR=0.125, 95% CI 0.016 to 0.955; P=0.007), while high-grade serous ovarian cancer was conversely associated with an increased likelihood of a BRCA1/2 mutation (OR=5.128, 95% CI 1.431 to 18.370; P=0.012). At the 10% threshold, 43.0% (142/330) of patients were indicated for testing under MSS3, compared with 35.8% (118/330) for MSS1% and 36.4% (120/330) for MSS2. At the 10% threshold, MSS3 sensitivity was 91.5% and specificity 65.0%, significantly better than the previous MSS1 (P=0.037) and MSS2 (P=0.032) models.ConclusionOur results indicate that the updated MSS3 outperforms previous iterations and relative to the Manchester population, is just as effective in identifying patients with BRCA1/2 mutations in a Southeast Asian population.